Functional Analysis of a Carotid Intima-Media Thickness Locus Implicates BCAR1 and Suggests a Causal Variant. (October 2015) - Boardman-Pretty, Freya; Smith, Andrew J.P.; Cooper, Jackie; Palmen, Jutta; Folkersen, Lasse; Hamsten, Anders; Catapano, Alberico L.; Melander, Olle; Price, Jacqueline F.; Kumari, Meena; Deanfield, John E.; Kivimäki, Mika; et al.
Abstract : Background—: Carotid intima-media thickness (IMT) is a marker of subclinical atherosclerosis that can predict cardiovascular disease events over traditional risk factors. This study examined the BCAR1-CFDP1-TMEM170A locus on chromosome 16, associated with carotid IMT and coronary artery disease in the IMT and IMT-Progression as Predictors of Vascular Events (IMPROVE) cohort, to identify the functional variant. Methods and Results—: In analysis of the locus lead single nucleotide polymorphism (SNP; rs4888378, intronic in CFDP1 ) in Progressione della Lesione Intimale Carotidea (PLIC), the protective AA genotype was associated with slower IMT progression in women ( P =0.04) but not in men. Meta-analysis of 5 cohort studies also supported a protective effect of the A allele on common carotid IMT in women only (women: β=−0.0047, P =1.63×10 –4 ; men: β=−0.0029, P =0.0678). Two hundred fourteen noncoding variants in strong linkage disequilibrium ( r 2 ≥0.8) with rs4888378 were identified from 1000 Genome Project. ENCODE regulatory chromatin marks were used to create a shortlist of 6 possible regulatory variants. Electrophoretic mobility shift assays on the shortlist detected allele-specific protein binding to the lead SNP rs4888378; multiplexed competitor electrophoretic mobility shift assays implicated FOXA as the protein. Luciferase reporter assays on rs4888378 showed a significant 35% to 92% ( P =0.0057; P =4.0×10 –22 ) decrease in gene expression with the A allele. Expression quantitative trait loci analysis confirmed previously reported associations of rs4888378 with BCAR1 in vascular tissues. Conclusions—: Molecular studies suggest the lead SNP as a potentially causal SNP at the BCAR1 - CFDP1 - TMEM170A locus, and expression quantitative trait loci studies implicate BCAR1 as the causal gene. This variant showed stronger effects on common carotid IMT in women, raising questions about the mechanism of the causal SNP on atherosclerosis. Abstract : Supplemental Digital Content is available in the text.